Thermal Protection System Design of a Reusable Launch Vehicle Using Integral Soft Objects - Andrea Aprovitola; Luigi Iuspa; Antonio Viviani (International Journal of Aerospace Engineering)
In the present paper, a modelling procedure of the thermal protection system designed for a conceptual Reusable Launch Vehicle is presented. A special parametric model, featuring a scalar field irradiated by a set of bidimensional soft objects, is developed and used to assign an almost arbitrary distribution of insulating materials over the vehicle surface. The model fully exploits the autoblending capability of soft objects and allows a rational distribution of thermal coating materials using a limited number of parameters. Applications to different conceptual vehicle configurations of an assigned thickness map, and material layout show the flexibility of the model. The model is finally integrated in the framework of a multidisciplinary analysis to perform a trajectory-based TPS sizing, subjected to fixed thermal constraints.